Dielectric material and preparation method and application thereof
By using BaTiO3 core and MgO, M1, M2 coatings in ceramic electronic components, combined with the bishell structure of (Ca(1-x-y)BaxSry)ZrO3 and R2O3, the stability of ceramic electronic components in high temperature and high pressure environment is solved. The dielectric material with high dielectric constant and long life is achieved.
Patent Information
- Application Number
- CN202411314168.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-20
AI Technical Summary
Existing ceramic electronic components have poor performance stability in high temperature or high pressure environments, and it is difficult to meet the needs of high capacity and high pressure products.
Using BaTiO3 as the core, the first cladding layer of MgO, M1, M2 is coated, and a second cladding layer of (Ca(1-x-y)BaxSry)ZrO3 and R2O3 is formed thereon, forming a bishell structure to improve the High temperature, high voltage stability and dielectric constant of dielectric materials.
It realizes high stability and high dielectric constant of dielectric materials at high temperatures and high pressures, extends the service life of the material, and improves the voltage resistance and dielectric-temperature characteristics of MLCC products.
Smart Images

Figure BDA0005051644770000091 
Figure BDA0005051644770000101 
Figure BDA0005051644770000111
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ceramic materials, and specifically relates to a dielectric material and a preparation method and application thereof. Background Art
[0002] As one of the representatives of ceramic electronic components, multilayer ceramic capacitors (MLCCs) are widely used in various electronic devices due to their high reliability and low cost. Especially for thin and small electronic devices, multilayer ceramic capacitors need to develop in the direction of smaller size, higher capacity, higher performance and thinner layers to meet the increasingly advanced usage requirements.
[0003] At present, the dielectric materials used to manufacture this type of small-size, large-capacity MLCC are mainly BaTiO3 compounds. The dielectric layer formed by BaTiO3 material (referred to as BT) has a high dielectric constant, but BaTiO3 material is a typical ferroelectric material at room temperature. At high temperature (about 120°C), it changes from a tetragonal ferroelectric phase to a cubic paraelectric phase, and the dielectric constant of the material changes dramatically, first rising rapidly and then falling sharply with the temperature, resulting in poor performance stability of MLCC products prepared from BaTiO3 materials under high temperature or high pressure use environments. At the same time, BaTiO3 materials have large polarization characteristics, resulting in low breakdown field strength of MLCC products prepared from them, which is difficult to meet the use requirements of high-capacity and high-voltage products. The (BaCaSr)ZrO3 material obtained by A-site doping is a non-ferroelectric phase material with a flat dielectric-temperature characteristic curve. The dielectric performance stability of the material is good at high temperature, but the dielectric constant of the material is very low and cannot be used in high-capacity products. Therefore, it is urgent to develop a ceramic dielectric material that can prepare MLCC products with high voltage resistance, high temperature stability and high dielectric constant. Summary of the invention
[0004] In order to overcome the problems existing in the prior art, one of the objectives of the present invention is to provide a dielectric material.
[0005] A second object of the present invention is to provide a method for preparing a dielectric material.
[0006] A third object of the present invention is to provide a chip-type multilayer ceramic capacitor.
[0007] A fourth object of the present invention is to provide application of the above dielectric material and / or chip-type multilayer ceramic capacitor in electronic equipment.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] The first aspect of the present invention provides a dielectric material, comprising a core, a first coating layer coated on the surface of the core, and a second coating layer coated on the surface of the first coating layer; the core comprises BaTiO3; the first coating layer comprises MgO, M1, and M2; the second coating layer comprises (Ca (1-x-y) Ba x Sr y )ZrO3 and R2O3;
[0010] The (Ca (1-x-y) Ba x Sr y )ZrO3, 0≤x≤1, 0≤y≤1;
[0011] The M1 is an oxide selected from at least one of Mn, Fe, Co, Cr, Ni, Mo, W, and V;
[0012] The M2 is an oxide selected from at least one of Si, Al, B and Li;
[0013] The R is selected from at least one of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Y.
[0014] In the dielectric material of the present invention, the core is BaTiO3, which has ferroelectric properties and a high dielectric constant, so that the dielectric material has a high dielectric constant, so that the chip-type multilayer ceramic capacitor made of the dielectric material has a high capacity characteristic; the first coating layer contains MgO, M1 and M2, and the second coating layer contains (Ca (1-x-y) Ba x Sr y )ZrO3 and R2O3 are paraelectric phase structures, which make the MLCC products made of dielectric materials have excellent stability under high temperature and high pressure. In addition, the (Ca (1-x-y) Ba x Sr y )ZrO3 has high breakdown field strength and highly stable dielectric-temperature characteristics, which can increase the activation energy of oxygen vacancy migration in dielectric materials, thereby reducing the capacitance change rate of MLCC prepared from dielectric materials at different temperatures and extending the service life of the material.
[0015] The first coating layer and the second coating layer in the present invention can improve the reliability, dielectric strength and temperature stability of MLCC products prepared from dielectric materials.
[0016] Preferably, the BaTiO3 is in a tetragonal phase. The tetragonal BaTiO3 has excellent ferroelectric properties and a high dielectric constant.
[0017] Preferably, based on the molar percentage of BaTiO3 being 100%, the molar percentage of MgO is 0.5-10%, the molar percentage of M1 is 0.1-5%, the molar percentage of M2 is 0.1-10%, and the molar percentage of (Ca (1-x-y) Ba x Sr y )The molar percentage of ZrO3 is 0.5-15%, and the molar percentage of R2O3 is 0.1-5%.
[0018] In the present invention, the molar percentage of MgO is 0.5-10%. For example, the molar percentage of MgO can be selected from 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%. More preferably, the molar percentage of MgO is 1-6%. In the present invention, MgO can prevent (Ca (1-x-y) Ba x Sr y )ZrO3 diffuses into the core and dissolves in BaTiO3, avoiding the formation of a uniform compound of the (CaBaSr)(TiZr)O3 system, and failing to form a second coating layer. When the MgO content is too high (for example, greater than 10%), the sinterability of the material decreases, hindering the solid solution of the element, the first coating layer becomes thinner, and the activation energy of oxygen vacancy migration in the dielectric material decreases, thereby deteriorating the reliability of the MLCC products prepared from the dielectric material; when the MgO content is too low (for example, less than 0.5%), the hindering effect of Mg is weakened, (CaBaSr)ZrO3 is easily dissolved in the BaTiO3 core, and even forms a uniform phase, failing to form a second coating layer, resulting in poor pressure resistance and capacity stability at high temperatures for the MLCC products prepared from the dielectric material.
[0019] In the present invention, the (Ca (1-x-y) Ba x Sr y ) The molar percentage of ZrO3 is 0.5 to 15%. For example, the (Ca (1-x-y) Ba x Sr y )The mole percentage of ZrO3 can be selected from 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%; further preferably, the (Ca (1-x-y) Ba x Sry )ZrO3 has a molar percentage of 1 to 10%. In the present invention, when (Ca (1-x-y) Ba x Sr y )When the content of ZrO3 is too high (for example, more than 15%), the proportion of the second coating layer is too high, and the dielectric constant of the second coating layer is low, resulting in a significant decrease in the overall dielectric constant of the MLCC product prepared from the dielectric material; when (Ca (1-x-y) Ba x Sr y ) When the ZrO3 content is too low (for example, less than 0.5%), the thickness of the second coating layer is too thin, and the breakdown field strength and dielectric-temperature characteristics of the MLCC product prepared from the dielectric material deteriorate.
[0020] In the present invention, (Ca (1-x-y) Ba x Sr y )ZrO3, 0≤x≤1, 0≤y≤1; for example, x can be selected from 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28, 0.3, 0.32, 0.34, 0.36, 0.38, 0.4, 0.42, 0.44, 0.46, 0.48, 0.5, 0.52, 0.54, 0.56, 0.58, 0.6, 0.62, 0.64, 0.66, 0.68, 0.7, 0.72, 0.74, 0.76, 0.78, 0.8, 0.82, 0.84, 0.86, 0.88, 0.9, 0.92, 0.94, 0 .96, 0.98, 1; y can be selected from 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28, 0.3, 0.32, 0.34, 0.36, 0.38, 0.4, 0. 42, 0.44, 0.46, 0.48, 0.5, 0.52, 0.54, 0.56, 0.58, 0.6, 0.62, 0.64, 0.66, 0.68, 0.7, 0.72, 0.74, 0.76, 0.78, 0.8, 0.82, 0.84, 0.86, 0.88, 0.9, 0.92, 0.94, 0.96, 0.98, 1. Preferably, the (Ca (1-x-y) Ba x Sr y )ZrO3 is selected from (Ca 0.5 Ba 0.2 Sr0.3 )ZrO3、(Ca 0.1 Ba 0.1 Sr 0.8 )ZrO3、(Ca 0.1 Ba 0.2 Sr 0.7 )ZrO3、(Ca 0.3 Ba 0.3 Sr 0.4 )ZrO3、(Ca 0.1 Ba 0.4 Sr 0.5 )ZrO3、(Ca 0.2 Ba 0.5 Sr 0.3 )ZrO3、(Ca 0.2 Ba 0.6 Sr 0.2 )ZrO3、(Ca 0.1 Ba 0.6 Sr 0.3 )ZrO3、(Ca 0.2 Ba 0.7 Sr 0.1 )ZrO3、(Ca 0.1 Ba 0.8 Sr 0.1 )ZrO3、(Ca 0.05 Ba 0.9 Sr 0.05 )ZrO3、(Ca 0.7 Ba 0.2 Sr 0.1 )ZrO3、(Ca 0.8 Ba 0.1 Sr 0.1 )ZrO3、(Ca 0.9 Ba 0.05 Sr 0.05 )ZrO3、(Ca 0.05 Ba 0.05 Sr 0.9 )ZrO3, CaZrO3, SrZrO3, BaZrO3, (Ca 0.5 Ba 0.5 )ZrO3 or (Ca 0.5 Sr 0.5 )ZrO3. The above (Ca (1-x-y) Ba x Sr y )ZrO3 has high breakdown field strength and highly stable dielectric-temperature characteristics, which can increase the activation energy of oxygen vacancy migration in dielectric materials, thereby reducing the capacitance change rate of MLCC prepared from dielectric materials at different temperatures and extending the service life of the material.
[0021] In the present invention, the molar percentage of R2O3 is 0.1-5%. For example, the molar percentage of R2O3 can be selected from 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8%, and 5%. In the present invention, when the content of R2O3 is too much (for example, greater than 5%), after sintering into MLCC products, the rare earth element R is too much solid solution, the first coating layer area becomes thicker, and the core proportion becomes smaller, resulting in a decrease in the dielectric constant of the MLCC product prepared from the dielectric material at room temperature; when the content of R2O3 is too little (for example, less than 0.1%), the first coating layer is difficult to form, resulting in the insulation resistance of the MLCC product prepared from the dielectric material deteriorating at high temperature, shortening the service life, and worsening the temperature characteristics.
[0022] In the present invention, the molar percentage of M1 is 0.1-5%. For example, the molar percentage of M1 can be selected from 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8%, 5%. In the present invention, when the content of M1 is too much (for example, greater than 5%), semiconductivity is likely to occur, resulting in reduced insulation resistance of the MLCC product prepared from the dielectric material, and low aging rate and DC bias characteristics; when the content of M1 is too little (for example, less than 0.1%), the anti-reduction performance decreases, resulting in Ti 4+ The dielectric material is reduced, resulting in a significant deterioration in the high-temperature and high-voltage insulation resistance performance of the MLCC products made from the dielectric material.
[0023] In the present invention, the molar percentage of M2 is 0.1-10%, for example, the molar percentage of M2 can be selected from 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%. In the present invention, when the content of M2 is too much (for example, greater than 10%), when sintering into MLCC products, there is too much sintering liquid phase, the grains are easy to grow, and the life characteristics deteriorate significantly; when the content is too little (for example, less than 0.1%), the sintering property decreases, and a higher temperature sintering is required, and the insulation resistance of the MLCC product prepared by the dielectric material is reduced.
[0024] The second aspect of the present invention provides a method for preparing the dielectric material provided in the first aspect of the present invention, comprising the following steps:
[0025] S1: adding magnesium salt, salt of M1 and salt of M2 to a suspension of barium titanate, mixing, drying and pre-calcining to obtain a ceramic powder having a first coating layer;
[0026] S2: The ceramic powder having the first coating layer, (Ca (1-x-y) Ba x Sr y )ZrO3 and R2O3 are mixed and ground, and then calcined to obtain the medium powder.
[0027] When preparing dielectric powder, MgO can begin to dissolve into the core of BaTiO3 at a relatively low temperature. However, due to the slow diffusion rate of Mg in BaTiO3 grains, its solid solubility is relatively low and mainly concentrated in the outer area of BaTiO3. (1-x-y) Ba x Sr y When ZrO3 begins to dissolve, MgO has not yet diffused well, which hinders the dissolution of the two. The dissolution rate of rare earth element R is faster than that of (Ca (1-x-y) Ba x Sr y )ZrO3, thus forming R2O3 and (Ca (1-x-y) Ba x Sr y )ZrO3 composite second coating layer, thereby improving the performance of MLCC products made of dielectric materials under high temperature and high pressure.
[0028] Preferably, the preparation method of the barium titanate suspension is: mixing barium titanate powder with at least one solvent selected from water, ethanol, and glacial acetic acid, and grinding to obtain the suspension.
[0029] Preferably, the barium titanate powder is prepared by a method selected from a solid phase method, a coprecipitation method, a hydrothermal method or an oxalate method.
[0030] Preferably, the magnesium salt is selected from at least one of magnesium nitrate, magnesium carbonate and magnesium acetate.
[0031] Preferably, the salt of M1 is selected from at least one of the nitrate of M1, the carbonate of M1 and the acetate of M1.
[0032] Preferably, the salt of M2 is selected from at least one of the nitrate of M2, the carbonate of M2 and the acetate of M2.
[0033] Preferably, the drying temperature in step S1 is 100-300°C, for example, it can be selected from 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, and 400°C; further preferably, the drying temperature in step S1 is 120-200°C.
[0034] Preferably, the drying time in step S1 is 2 to 10 hours, for example, can be selected from 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, and 10 hours; further preferably, the drying time in step S1 is 4 to 8 hours.
[0035] Preferably, the pre-firing temperature in step S1 is 400-800°C, for example, can be selected from 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, 620°C, 640°C, 660°C, 680°C, 700°C, 720°C, 740°C, 760°C, 780°C, 800°C; further preferably, the pre-firing temperature in step S1 is 500-700°C.
[0036] Preferably, the pre-burn-in time in step S1 is 0.5 to 3 h, for example, can be selected from 0.5 h, 0.8 h, 1 h, 1.2 h, 1.5 h, 1.8 h, 2 h, 2.2 h, 2.5 h, 2.8 h, 3 h; further preferably, the pre-burn-in time in step S1 is 1 to 2.5 h.
[0037] Preferably, the calcination temperature in step S2 is 500-1000°C, for example, can be selected from 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C; further preferably, the calcination temperature in step S2 is 600-900°C.
[0038] Preferably, the calcination time in step S2 is 1 to 4 h, for example, can be selected from 1 h, 1.2 h, 1.5 h, 1.8 h, 2 h, 2.2 h, 2.5 h, 2.8 h, 3 h, 3.2 h, 3.5 h, 3.8 h, 4 h; further preferably, the calcination time in step S2 is 1 to 3 h.
[0039] Preferably, the step S2 is: the ceramic powder having the first coating layer, (Ca (1-x-y) Ba x Sr y )ZrO3 and R2O3 are mixed and ground, wet-crushed, dried, and then calcined to obtain the medium powder.
[0040] Preferably, the wet pulverization time in step S2 is 4 to 12 hours, for example, it can be selected from 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, and 12 hours.
[0041] Preferably, the drying temperature in step S2 is 100-400°C, for example, can be selected from 100°C, 200°C, 300°C, 400°C.
[0042] Preferably, the drying time in step S2 is 150 to 300 min, for example, can be selected from 150 min, 170 min, 190 min, 200 min, 220 min, 240 min, 260 min, 280 min, and 300 min.
[0043] Preferably, the grinding step in step S2 is ball milling.
[0044] When the dielectric material of the present invention is prepared, the elements in the raw materials diffuse and dissolve in BaTiO3 (i.e., BT), wherein Mg ions begin to dissolve at low temperatures, but their diffusion rate in BT is low, which hinders the diffusion of rare earth ions R and (Ca (1-x-y) Ba x Sr y )Diffusion of ZrO3, thus forming a double shell structure.
[0045] The third aspect of the present invention provides a chip-type multilayer ceramic capacitor, comprising a dielectric layer, wherein the dielectric layer is made of the dielectric material described in the first aspect of the present invention.
[0046] Preferably, the chip-type multilayer ceramic capacitor includes a laminated body including a dielectric layer and an internal electrode layer stacked in sequence.
[0047] Preferably, an external electrode is respectively provided at two ends of the stacked body, and the external electrode is electrically connected to the internal electrode layer.
[0048] Preferably, a plating layer is provided on the surface of the outer electrode layer.
[0049] Preferably, the plating layer includes a first plating layer disposed on the surface of the outer electrode and a second plating layer disposed on the surface of the first plating layer.
[0050] Preferably, the method for preparing the chip-type multilayer ceramic capacitor comprises the following steps:
[0051] Forming a ceramic slurry containing the dielectric material into a film to obtain a ceramic green sheet;
[0052] forming a conductive film on the ceramic green sheet, laminating, heat treating, and sintering to obtain the laminate;
[0053] External electrodes are formed at both ends of the stacked body, and plated films are formed on the surfaces of the external electrodes to obtain the chip-type multilayer ceramic capacitor.
[0054] Preferably, the ceramic slurry comprises a dielectric material, an organic binder and an organic solvent in a mass ratio of 100:(7-10):(40-60).
[0055] Preferably, the step of forming a film of the ceramic slurry containing the dielectric material is specifically: forming a film of the ceramic slurry by any method selected from the group consisting of a lip coating method and a doctor blade method.
[0056] Preferably, the heat treatment temperature is 250-350°C.
[0057] Preferably, the sintering atmosphere is a strongly reducing atmosphere; further preferably, the sintering atmosphere is a strongly reducing atmosphere in which the volume ratio of hydrogen to nitrogen is (0.1-2):100.
[0058] Preferably, the sintering temperature is 1100-1300°C.
[0059] Preferably, the sintering time is 2 to 4 hours.
[0060] Preferably, the step of forming external electrodes at both ends of the stacked body comprises: coating external electrode slurry at both ends of the stacked body respectively, and then baking at a temperature of 600 to 900° C. for 2 to 4 hours.
[0061] The fourth aspect of the present invention provides the use of the dielectric material described in the first aspect of the present invention and / or the chip-type multilayer ceramic capacitor described in the third aspect of the present invention in electronic equipment.
[0062] The beneficial effects of the present invention are as follows: the dielectric material of the present invention uses barium titanate as the core, and barium titanate has ferroelectric properties and a high dielectric constant, which can make the dielectric material maintain a high dielectric constant, and uses MgO as the first coating layer, which can prevent R2O3 and (Ca (1-x-y) Ba x Sr y )ZrO3 infiltrates into the core, which results in the inability to form a double shell structure. (1-x-y) Ba x Sr y )ZrO3 material is used as the second coating layer, which has a paraelectric phase structure, so that the MLCC products prepared from the dielectric material have excellent stability under high temperature and high pressure. Therefore, the dielectric material in the present invention also has high dielectric strength, high dielectric constant, and excellent dielectric-temperature characteristics, and can be used to make high-voltage and high-capacity chip-type multilayer ceramic capacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 This is the TEM-EDS image of the chip-type multilayer ceramic capacitor prepared using the dielectric material in Comparative Example 1.
[0064] Figure 2 TEM-EDS image of a chip-type multilayer ceramic capacitor prepared using the dielectric material in Example 1. DETAILED DESCRIPTION
[0065] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0066] In the dielectric material of the present invention, when the materials in the first cladding layer and the second cladding layer meet the following requirements, such as: the molar percentage of MgO is 0.5-10%; (Ca (1-x-y) Ba x Sr y )ZrO3, 0≤x≤1, 0≤y≤1, the molar percentage is 0.5-15%; M1 is selected from at least one oxide of Mn, Fe, Co, Cr, Ni, Mo, W, V, the molar percentage is 0.1-5%; M2 is selected from at least one oxide of Si, Al, B, Li, the molar percentage is 0.1-10%; R is selected from at least one of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, the molar percentage of R2O3 is 0.1-5%, all of which can make the chip multilayer capacitor using the dielectric material as the raw material for preparing the dielectric layer meet the following requirements at the same time: dielectric constant ≥2500, breakdown field strength ≥40V / μm, 50% mean time to failure (MTTF) ≥3h, TCC within ±15%. In order to facilitate the description of the technical solution in the present invention, only (Ca (1-x-y) Ba x Sr y )ZrO3 is (Ca 0.5 Ba 0.2 Sr 0.3 )ZrO3, CaZrO3, SrZrO3, BaZrO3, (Ca 0.5 Ba 0.5 )ZrO3、(Ca 0.5 Sr 0.5 )ZrO3、(Ca 0.1 Ba 0.4 Sr 0.5) Several specific embodiments of ZrO3, M1 is MnO2, M2 is SiO2, and R2O3 is Dy2O3.
[0067] The present invention uses ICP, XRF and other detection means to detect the element composition and content of the sintered products in the following embodiments and comparative examples, and uses TEM to test the core-double-shell structure of the sintered products in the embodiments and comparative examples.
[0068] Example 1
[0069] This example provides a dielectric material, including a core, a first cladding layer, and a second cladding layer;
[0070] The first coating layer is coated on the surface of the core, and the second coating layer is coated on the surface of the first coating layer; the core is BaTiO3, the first coating layer is a composite oxide layer of MgO, MnO2, and SiO2, and the second coating layer is (Ca 0.5 Ba 0.2 Sr 0.3 )Composite oxide layer of ZrO3 and Dy2O3.
[0071] Taking the molar percentage of the inner core BaTiO3 as 100%, the molar percentage of MgO is 4%, the molar percentage of MnO2 (i.e. M1) is 1%, the molar percentage of SiO2 (i.e. M2) is 4%, the molar percentage of Dy2O3 (i.e. R2O3) is 3%, (Ca 0.5 Ba 0.2 Sr 0.3 )The molar percentage of ZrO3 is 6%, as shown in Table 1.
[0072] The dielectric material in this example is prepared by a preparation method comprising the following steps:
[0073] 1) Place BaTiO3 powder in pure water, stir, grind and disperse to obtain a suspension;
[0074] 2) Based on the molar percentage of BaTiO3 being 100 mol%, 4 mol% of magnesium acetate, 1 mol% of manganese acetate, and 4 mol% of silicon acetate are added to the above suspension solution, stirred and dispersed, to obtain a mixed solution containing the core and the first coating layer material;
[0075] 3) drying and pre-calcining the mixed solution obtained in step 2) to obtain BaTiO3 ceramic powder coated with MgO, MnO2 and SiO2, i.e., ceramic powder having a first coating layer; the drying temperature is 200°C, the drying time is 6h, the pre-calcining temperature is 600°C, and the pre-calcining time is 2h;
[0076] 4) Based on the molar percentage of BaTiO3 being 100 mol%, 6 mol% of (Ca 0.5 Ba0.2 Sr 0.3 ) ZrO3 and 3 mol% Dy2O3 powders are mixed with the ceramic powder with the first coating layer obtained in step 3), wet-crushed for 6 hours, dried at 200°C for 200 minutes, and calcined at 750°C for 2 hours to obtain the dielectric material in this example.
[0077] Embodiments 2 to 6
[0078] The dielectric materials in Examples 2 to 6 are different from those in Example 1 only in that the molar percentage of MgO in the first coating layer is different, as shown in Table 1.
[0079] Embodiment 7-8
[0080] The only difference between the dielectric materials in Examples 7 to 8 and Example 1 is that the molar percentage of MnO2 in the first coating layer is different, as shown in Table 1.
[0081] Embodiments 9-10
[0082] The only difference between the dielectric materials in Examples 9 to 10 and Example 1 is that the molar percentage of SiO2 in the first cladding layer is different, as shown in Table 1.
[0083] Examples 11 to 13
[0084] The dielectric materials in Examples 11 to 13 are different from those in Example 1 only in that the molar percentage of Dy2O3 in the second coating layer is different, as shown in Table 1.
[0085] Embodiments 14 to 19
[0086] The dielectric materials in Examples 14 to 19 differ from those in Example 1 only in that: 0.5 Ba 0.2 Sr 0.3 )The molar percentage of ZrO3 is different, as shown in Table 1.
[0087] Comparative Examples 1 to 3
[0088] The dielectric materials in Comparative Examples 1 to 3 are different from those in Example 1 only in that the molar percentage of MgO in the first coating layer is different, as shown in Table 1.
[0089] Comparative Examples 4-5
[0090] The dielectric materials in Comparative Examples 4 to 5 are different from those in Example 1 only in that the molar percentage of Dy2O3 in the second coating layer is different, as shown in Table 1.
[0091] Comparative Examples 6 to 8
[0092] The dielectric materials in Comparative Examples 6 to 8 differ from those in Example 1 only in that: 0.5 Ba 0.2 Sr 0.3 )The molar percentage of ZrO3 is different, as shown in Table 1.
[0093] The dielectric materials in Examples 2 to 19 and Comparative Examples 1 to 8 were all prepared by referring to the preparation method in Example 1.
[0094] Table 1: Composition ratio of dielectric materials in Examples 1 to 19 and Comparative Examples 1 to 8
[0095]
[0096] Embodiments 20 to 23
[0097] The preparation method of the dielectric material in Examples 20 to 23 is different from that in Example 1 only in that the pre-firing temperature in step 3) is different, as shown in Table 2.
[0098] Embodiments 24 to 27
[0099] The only difference between the preparation methods of the dielectric materials in Examples 24 to 27 and Example 1 is that the pre-burning time in step 3) is different, as shown in Table 2.
[0100] Embodiments 28 to 31
[0101] The preparation method of the dielectric material in Examples 28 to 31 is different from that in Example 1 only in that the calcination temperature in step 4) is different, as shown in Table 2.
[0102] Embodiments 32 to 35
[0103] The preparation method of the dielectric material in Examples 32 to 35 is different from that in Example 1 only in that the calcination time in step 4) is different, as shown in Table 2.
[0104] Comparative Examples 9 to 10
[0105] The preparation method of the dielectric material in Comparative Examples 9 to 10 is different from that in Example 1 only in that the pre-firing temperature in step 3) is different, as shown in Table 2.
[0106] Comparative Examples 11-12
[0107] The preparation method of the dielectric material in Comparative Examples 11 to 12 is different from that in Example 1 only in that the pre-firing time in step 3) is different, as shown in Table 2.
[0108] Comparative Examples 13-14
[0109] The preparation method of the dielectric material in Comparative Examples 13 to 14 is different from that in Example 1 only in that the calcination temperature in step 4) is different, as shown in Table 2.
[0110] Comparative Examples 15-16
[0111] The preparation method of the dielectric material in Comparative Examples 15 to 16 is different from that in Example 1 only in that the calcination time in step 4) is different, as shown in Table 2.
[0112] The dielectric materials in Examples 20 to 35 and Comparative Examples 9 to 16 have the same structure and composition ratio as the dielectric material in Example 1.
[0113] Table 2 Preparation parameters of dielectric materials in Examples 20 to 35 and Comparative Examples 9 to 16
[0114]
[0115]
[0116] Embodiments 36 to 41
[0117] The dielectric materials in Examples 36 to 41 differ from those in Example 1 only in that Examples 36 to 41 use equal molar percentages of CaZrO3, SrZrO3, BaZrO3, (Ca 0.5 Ba 0.5 )ZrO3、(Ca 0.5 Sr 0.5 )ZrO3、(Ca 0.1 Ba 0.4 Sr 0.5 )ZrO3 replaces (Ca) in Example 1 0.5 Ba 0.2 Sr 0.3 )ZrO3, as shown in Table 3.
[0118] Table 3 Composition ratio of dielectric materials in Examples 36 to 41
[0119]
[0120] Preparation of chip multilayer ceramic capacitors:
[0121] (1) The dielectric materials in Examples 1 to 41 and Comparative Examples 1 to 16 are respectively put into a sand mill with polyvinyl butyral (PVB) and ethanol in a mass ratio of 100:10:50, and then wet-mixed to prepare a ceramic dielectric slurry. The ceramic dielectric slurry is molded by a lip coating method to prepare a ceramic dielectric green sheet.
[0122] (2) Then, a conductive paste for internal electrodes mainly composed of a base metal material such as Ni is prepared, and the conductive paste for internal electrodes is screen-printed on a ceramic dielectric green sheet to form a conductive film of a predetermined pattern on the surface of the ceramic dielectric green sheet.
[0123] (3) Multiple ceramic dielectric green sheets with conductive films formed thereon are stacked in a given direction, and ceramic dielectric green sheets without conductive films formed thereon are arranged on the uppermost layer, and the sheets are pressed and bonded, and cut into a given size to produce a ceramic laminate. The ceramic laminate is then heat treated at 300°C in an air atmosphere to decompose and remove the binder, and then sintered at 1200°C for 2 hours in a strong reducing atmosphere composed of a gas having a volume ratio of H2:N2 of 0.005:1, to obtain a ceramic sintered body.
[0124] (4) A conductive paste for external electrodes (mainly composed of Ag) is applied to both end surfaces of the ceramic sintered body and baked at 750°C for 2 hours to form external electrodes. The conductive material contained in the conductive paste for external electrodes is not particularly limited, but from the perspective of cost reduction, it is preferred to use a material mainly composed of Ag, Cu, or an alloy thereof.
[0125] In addition, as a common method for preparing external electrodes, a conductive paste for external electrodes may be applied to both end surfaces of a ceramic laminate and then fired together with the ceramic laminate.
[0126] (5) Finally, electrolytic plating is performed to form a first plating film composed of Ni, Cu, Ni-Cu alloy, etc. on the surface of the external electrode, and then a second plating film composed of solder, tin, etc. is formed on the surface of the first plating film to produce a chip-type multilayer ceramic capacitor.
[0127] Then, the dielectric constant, breakdown field strength, accelerated life test, and TCC performance of the multilayer ceramic capacitors made of the dielectric materials in Examples 1 to 41 and Comparative Examples 1 to 16 were tested respectively. The specific test methods are shown in Table 4 below.
[0128] Table 4 Performance test items, test conditions, standards and requirements
[0129]
[0130] The performance data of the multilayer ceramic capacitors made of the dielectric materials in Examples 1 to 19 and Comparative Examples 1 to 8 measured according to the above test method are shown in Table 5 below, the performance data of the multilayer ceramic capacitors made of the dielectric materials in Examples 20 to 35 and Comparative Examples 9 to 16 are shown in Table 6 below, and the performance data of the multilayer ceramic capacitors made of the dielectric materials in Examples 36 to 41 are shown in Table 7 below.
[0131] Table 5 Performance data of multilayer ceramic capacitors of Examples 1 to 19 and Comparative Examples 1 to 8
[0132]
[0133]
[0134] As shown in Table 5, compared with Comparative Examples 1 to 8, Examples 1 to 19 of the present invention adjust the contents of MgO, MnO2, and SiO2 in the first coating layer and the contents of (Ca 0.5 Ba 0.2 Sr 0.3 )ZrO3 and Dy2O3 content, so that the dielectric constant of the prepared multilayer ceramic capacitor is ≥2500, the breakdown field strength is ≥40V / μm, the 50% mean time to failure (MTTF) is ≥3h, and the TCC is ≤±15%, which meets the use requirements of high-capacity and high-voltage MLCC. The specific analysis is as follows:
[0135] By comparing Examples 1 to 6 with Comparative Examples 1 to 3, it can be seen that since the first coating layer of BaTiO3 contains MgO, when the dielectric material is sintered into the dielectric layer of the MLCC product, Mg ions can be dissolved into BaTiO3 at a lower temperature, but their diffusion rate in BaTiO3 is slow, which has a great influence on the rare earth ions and (Ca) in the original second coating layer. 0.5 Ba 0.2 Sr 0.3 )It has an inhibitory effect on the solid solution and diffusion of ZrO3, so that the core-double-shell structure can still be maintained after sintering, especially the rare earth-doped calcium barium strontium zirconate material in the second coating layer, so that the pressure resistance and dielectric-temperature characteristics of the MLCC products prepared from the dielectric material of the present invention are improved. Therefore, appropriately increasing the MgO content in the first coating layer of the dielectric material is conducive to the formation of the second coating layer, which is beneficial to improving the pressure resistance, temperature characteristics and service life of the MLCC products. However, when the MgO content is too low (for example: Comparative Example 1 does not contain MgO), the core-double-shell structure cannot be formed, which reduces the temperature stability, breakdown field strength and service life of the MLCC products made of the dielectric material. A transmission electron microscope was used to perform EDS energy spectrum analysis on the multilayer chip ceramic capacitors prepared from the dielectric materials of Comparative Example 1 and Example 1 to confirm the element distribution. The specific test results are as follows. Figure 1 and Figure 2 As shown. Figure 1 and Figure 2 It can be seen that the rare earth Dy elements all form a shell structure, and the Mg and Mn elements are evenly distributed; the Ca, Sr and Zr elements of each grain in Example 1 overlap and are wrapped in the outer layer of Ba and Ti elements, which can be seen to form a (Ca(1-x-y) Ba x Sr y )ZrO3's second coating layer and a double-shell structure of the rare earth inner shell; while in Comparative Example 1, the elements Ca, Sr, Zr, Ba, Ti, etc. are evenly distributed, and no Ca, Sr, Zr shell is found, that is, a double-shell grain structure cannot be formed. In Comparative Example 1, there is no obstruction of MgO, and the (Ca) in the second coating layer is 0.5 Ba 0.2 Sr 0.3 )ZrO3 diffuses into the core layer and forms a homogeneous phase with BaTiO3; while Example 1 forms a phase containing (Ca 0.5 Ba 0.2 Sr 0.3 )The second coating layer of ZrO3; however, when the MgO content is too high, the Mg ions excessively hinder the diffusion of other elements, the solid solubility of rare earth ions in BaTiO3 decreases, the sinterability of the material decreases, and the grain growth is inhibited, resulting in a decrease in the dielectric constant and life of the MLCC product.
[0136] By comparing Examples 11 to 13 and Comparative Examples 4 to 5, it can be seen that the rare earth element Dy can be dissolved in the perovskite structure of ABO3, modify the perovskite material of ABO3, and form a core-double shell structure, which is helpful to improve the dielectric-temperature stability and service life of MLCC products; when the rare earth element Dy is doped too little, the first coating layer of the material is difficult to form, the life is shortened, and the temperature characteristics deteriorate due to the increase in the proportion of the barium titanate core; when the rare earth element Dy is doped too much, the proportion of the first coating layer and the second coating layer is too high, the barium titanate core with a high dielectric constant is reduced, and the room temperature dielectric constant of the MLCC product prepared from the dielectric material is reduced.
[0137] By comparing Examples 14 to 19 with Examples 6 to 8, it can be seen that (Ca 0.5 Ba 0.2 Sr 0.3 )The use of ZrO3 enables the dielectric material to form a second coating layer, which helps to improve the voltage resistance of the MLCC product; when (Ca 0.5 Ba 0.2 Sr 0.3 )When the ZrO3 content is too low, the second coating layer accounts for a small proportion, resulting in a decrease in the breakdown field strength of the MLCC product prepared from the dielectric material; when (Ca 0.5 Ba 0.2 Sr 0.3 )When the ZrO3 content is too high, the proportion of the second coating layer is high, the proportion of the paraelectric phase increases, and the dielectric constant of the MLCC product prepared from the dielectric material is reduced.
[0138] Table 6 Performance data of multilayer ceramic capacitors of Examples 20 to 35 and Comparative Examples 9 to 16
[0139]
[0140]
[0141] As shown in Table 6, Examples 20 to 35 of the present invention can improve the dielectric constant and breakdown field strength of the obtained multilayer ceramic capacitor, extend the MTTF time, and reduce the TCC effect by adjusting the pre-firing temperature and time, and the calcination temperature and time. The specific analysis is as follows:
[0142] By comparing Examples 20 to 23 with Comparative Examples 9 to 10, it can be seen that the pre-firing temperature affects the coating of the first coating layer containing MgO, which affects the solid solution effect and uniform distribution of Mg ions, thereby affecting the formation of the core-double-shell structure. When the pre-firing temperature is too low or too high, the MgO coating effect is poor or the solid solution is premature, which has an impact on the rare earth elements and (Ca (1-x-y) Ba x Sr y )The solid solution barrier effect of ZrO3 is not enough, which affects the formation of the core-double-shell structure and reduces the breakdown field strength of the MLCC products prepared from dielectric materials.
[0143] By comparing Examples 24 to 27 and Comparative Examples 11 to 12, it can be seen that the pre-firing time affects the formation and stability of the first coating layer containing MgO. When the pre-firing time is too short, the MgO coating is uneven, or even part of the first coating layer fails to form, and is in a free state, which affects the uniformity of the core formation of the shell phase and reduces the breakdown field strength of the MLCC product prepared from the dielectric material. When the pre-firing time is too long, the Mg ions are dissolved prematurely, and at the same time the sintering activity of the powder is reduced, and the density of the dielectric material becomes worse, resulting in a decrease in the breakdown field strength of the MLCC product prepared from the dielectric material.
[0144] By comparing Examples 28 to 31 and Comparative Examples 13 to 14, it can be seen that the calcination temperature affects (Ca 0.5 Ba 0.2 Sr 0.3 )The formation and uniformity of the ZrO3 layer. When the calcination temperature is too low, the second coating layer is not uniform, which affects the uniformity of the second coating layer and reduces the breakdown field strength of the MLCC products prepared from the dielectric material. When the calcination temperature is too high, the sintering activity of the powder deteriorates, the density of the dielectric material decreases, and the pores are high, which reduces the breakdown field strength of the MLCC products prepared from the dielectric material.
[0145] By comparing Examples 32 to 35 and Comparative Examples 15 to 16, it can be seen that the calcination time affects (Ca 0.5 Ba 0.2 Sr 0.3)ZrO3 layer formation and uniformity, when the calcination time is too short, the second coating layer formation effect is poor, affecting the uniformity of the second coating layer, there is part of the (Ca 0.5 Ba 0.2 Sr 0.3 ) The single ZrO3-enriched phase reduces the breakdown field strength of the MLCC products prepared from the dielectric material; when the calcination time is too long, the sintering activity of the powder deteriorates, the material density decreases, and the porosity is high, which reduces the breakdown field strength of the MLCC products prepared from the dielectric material.
[0146] Table 7 Performance data of multilayer ceramic capacitors of Examples 36 to 41
[0147]
[0148] It can be seen from Table 7 that the second coating layer of the dielectric material adopts (Ca (1-x-y) Ba x Sr y )When ZrO3 is coated, as long as x and y meet the following conditions: 0≤x≤1, 0≤y≤1, the dielectric constant and breakdown field strength of the multilayer ceramic capacitor made of this dielectric material can be improved, the MTTF time can be extended and the TCC can be reduced.
[0149] In summary, the dielectric material of the present invention is formed by coating a first coating layer containing MgO, M1, and M2 on a BaTiO3 core, and then coating a layer (Ca (1-x-y) Ba x Sr y )ZrO3, R2O3 composite oxide layer, and finally formed a double-layer shell-core structure dielectric material. During the calcination process, the high tetragonal phase of barium titanate core makes the dielectric material have a high dielectric constant, and the double-layer shell structure is a non-ferroelectric phase, especially (Ca (1-x-y) Ba x Sr y )The second coating layer of ZrO3 greatly improves the activation energy of oxygen vacancy migration in the dielectric material, so that the dielectric material has a high breakdown field strength and excellent dielectric-temperature characteristics, thereby obtaining a dielectric material for MLCC with high withstand voltage, high capacity and high reliability.
[0150] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A dielectric material, characterized in that: The invention comprises a core, a first coating layer coated on the surface of the core, and a second coating layer coated on the surface of the first coating layer; the core comprises BaTiO3; the first coating layer comprises MgO, M1, and M2; the second coating layer comprises (Ca (1-x-y) Ba x Sr y )ZrO3 and R2O3; The (Ca (1-x-y) Ba x Sr y )ZrO3, 0≤x≤1, 0≤y≤1; The M1 is an oxide selected from at least one of Mn, Fe, Co, Cr, Ni, Mo, W, and V; The M2 is an oxide selected from at least one of Si, Al, B and Li; The R is selected from at least one of La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and Y.
2. The dielectric material according to claim 1, characterized in that: Taking the molar percentage of BaTiO3 as 100%, the molar percentage of MgO is 0.5-10%, the molar percentage of M1 is 0.1-5%, the molar percentage of M2 is 0.1-10%, and the molar percentage of (Ca (1-x-y) Ba x Sr y )The molar percentage of ZrO3 is 0.5-15%, and the molar percentage of R2O3 is 0.1-5%.
3. The dielectric material according to claim 2, characterized in that: The molar percentage of MgO is 1-6%; And / or, the (Ca (1-x-y) Ba x Sr y )The molar percentage of ZrO3 is 1 to 10%.
4. The method for preparing a dielectric material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: adding magnesium salt, salt of M1 and salt of M2 to a suspension of barium titanate, mixing, drying and pre-calcining to obtain a ceramic powder having a first coating layer; S2: The ceramic powder having the first coating layer, (Ca (1-x-y) Ba x Sr y )ZrO3 and R2O3 are mixed and ground, and then calcined to obtain the medium powder.
5. The method for preparing a dielectric material according to claim 4, characterized in that: The drying temperature in step S1 is 100-300°C; And / or, the drying time in step S1 is 2 to 10 hours; And / or, the pre-firing temperature in step S1 is 400-800° C.; And / or, the pre-burning time in step S1 is 0.5 to 3 hours; And / or, the calcination temperature in step S2 is 500-1000°C; And / or, the calcination time in step S2 is 1 to 4 hours.
6. The method for preparing a dielectric material according to claim 4, characterized in that: The drying temperature in step S1 is 120-200°C; And / or, the drying time in step S1 is 4 to 8 hours; And / or, the pre-firing temperature in step S1 is 500-700° C.; And / or, the pre-burning time in step S1 is 1 to 2.5 hours; And / or, the calcination temperature in step S2 is 600-900° C.; And / or, the calcination time in step S2 is 1 to 3 hours.
7. The method for preparing a dielectric material according to claim 4, characterized in that: The step S2 is: the ceramic powder having the first coating layer, (Ca (1-x-y) Ba x Sr y )ZrO3 and R2O3 are mixed and ground, wet-crushed, dried, and then calcined to obtain the medium powder.
8. The method for preparing a dielectric material according to claim 7, characterized in that: The wet crushing time in step S2 is 4 to 12 hours; And / or, the drying temperature in step S2 is 100-400° C.; And / or, the drying time in step S2 is 150 to 300 minutes.
9. A chip-type multilayer ceramic capacitor, comprising a dielectric layer, characterized in that: The dielectric layer is made of a material according to any one of claims 1 to 3.
10. Use of the dielectric material according to any one of claims 1 to 3 and / or the chip-type multilayer ceramic capacitor according to claim 9 in electronic equipment.
Citation Information
Patent Citations
Perovskite powder, fabricating method thereof and multi-layer ceramic electronic parts
CN103130500A
Ceramic dielectric material of barium titanate core-strontium / zirconium / calcium shell structure and preparation method thereof
CN107739205A
Dielectric substance, electronic device and multilayer ceramic capacitor
CN113628879A
High-effective-capacity multilayer ceramic capacitor dielectric material and preparation method thereof
CN115116745A
Ceramic dielectric material as well as preparation method and application thereof
CN116813355A